Le intermittenze del lavoro: resistenza e rassegnazione in Francesco Targhetta e Danilo Masotti - Cataldi, Bianca Rita (Status Quaestionis, 2019)
In a recent paper, Romano Luperini claimed that contemporary Italy is currently undergoing a transition from a literature about the crisis (the literature of the first postmodernist generation of Eco and Tabucchi) to a crisis of literature. According to the critic, the causes of this phenomenon reside in several factors: globalisation, the contamination of Italian literature with other types of media (cinema, television, journalism and advertising), the weakening of literature’s own identity, the lack of a true political and social engagement and the disappearing of a “literary civilization based on the value and the sacrality of literature” (Luperini 2015). If this is true, how should we interpret the rise of a new Italian literary production that aims at recounting the economic crisis from the 2000s onwards? From Michela Murgia to Aldo Nove, from Giuseppe Falco to Mario Desiati, in the last twenty years Italian fiction has tried to retell the nation’s economic crisis, the precariousness of labour and the new forms of alienation in the workplace. Contrary to what one would expect, these literary works did not always succeed in giving a convincing representation of the historical time they wanted to describe. In this paper, through the analysis of two works belonging to this literary corpus – "Perciò veniamo bene nelle fotografie" by Francesco Targhetta and "Ci meritiamo tutto" by Danilo Masotti – I will retrace what is achieved and what is not in these two novels, which though different in style, share the same aim: to describe a betrayed generation that has been caught by surprise by an intermittent or alienating world of work, and appears always suspended between an attempt to resist and a temptation to surrender.